Laboratory Animals: Unification of Legislation in Europe - Rozemond, H. (WBI Studies Repository, 1982)
A committee of experts, Comite Ad Hoc pour Ia Protection des Animaux (CAHPA), has been convened by the Council of Europe to prepare a European convention on the protection of laboratory animals. The chief goal of the Council of Europe is to implement peaceful cooperation concerning cultural, economic, and social affairs in Europe. Matters of military concern are excluded. The countries represented on the Council include Austria, Belgium, Cyprus, Denmark, the Federal Republic of Germany, France, Greece, Great Britain, Iceland, Ireland, Italy, Liechtenstein, Luxembourg, Malta, the Netherlands, Norway, Spain, Turkey, Sweden, and Switzerland. The Council holds conventions on various topics of broad regional interest. Some of the most important documents produced by its conventions have included the Convention for the Protection of Human Rights and Fundamental Freedoms in 1950 and the European Social Charter in 1960.